1978
DOI: 10.1021/bi00616a006
|View full text |Cite
|
Sign up to set email alerts
|

Studies on transfer ribonucleic acids and related compounds. 22. Joining of 3'-modified oligonucleotides by T4 RNA ligase. Synthesis of a heptadecanucleotide corresponding to the bases 61-77 from Escherichia coli tRNA fMet

Abstract: Chemically synthesized fragments corresponding to the 3' end of tRNAfMet from Escherichia coli were joined by T4-induced RNA ligase to yield a heptadecanucleotide (bases 61--77). The 3' terminus of C-C-A was modified by introduction of the ethoxymethylidene group to prevent intra- and intermolecular self-joining reactions at the 3' end. The terminal trimer was phosphorylated using polynucleotide kinase and joined to C-A-A with RNA ligase. The hexamer [C-A-A-C-C-A(ethoxymethylidene)] corresponding to bases 72--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Nearest-neighbor analysis (17), 3'-and 5'-terminal analysis (20), and partial nuclease P1 digestion (22) for mobility shift analysis were as described. For complete RNase T1 digestion ofthe product (1 pmol), RNase T1 (1 unit) was used in the presence of phosphatase (180 microunits) in (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearest-neighbor analysis (17), 3'-and 5'-terminal analysis (20), and partial nuclease P1 digestion (22) for mobility shift analysis were as described. For complete RNase T1 digestion ofthe product (1 pmol), RNase T1 (1 unit) was used in the presence of phosphatase (180 microunits) in (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The 3'-phosphorylated heptadecamer 4 was prepared as described (22). The 3'-phosphorylation of C-A-A-C-C-A (16) was done with P1-adenosine-P2-(o-nitrobenzyl) pyrophosphate and RNA ligase (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason for the difference between the proportion of 5Ј L vRNA deletions observed by sequencing and that observed by primer extension may be due to a nucleotide preference of the RNA ligase. Several studies have shown that the efficiency of the joining reaction is dependent on the particular donor (5Ј) and acceptor (3Ј) terminal nucleotides and the secondary structure of the termini (6,7,13,25,30). While purine acceptors and pyrimidine donors are generally believed to be the optimum substrates and could account for the large percentage of full-length L vRNAs ligated, not all types and combinations of oligoribonucleotides have been examined.…”
Section: Fig 3 Northern Hybridization Analysis Of Sr-11 Vrna Duringmentioning
confidence: 99%
“…Polynucleotide kinase and E. coli alkaline phosphatase were obtained from Takara Shuzo and nuclease Sl from Sankyo. Other enzymes used for the analyses of products were obtained as in [14,19,20]. Crude E. coli aminoacyltRNA synthetase was purified as described [21].…”
Section: Ribooligonucleotidesmentioning
confidence: 99%